Evaluasi Dampak Dana Bagi Hasil Cukai Tembakau terhadap Kesejahteraan Buruh Rokok di Kudus - Awwaliya Putri; M. Nur Rofiq Addiansyah (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2026)
The tobacco industry plays a significant role in sustaining the local economy of Kudus Regency while simultaneously contributing to state revenue through excise taxation. This condition raises a policy issue regarding the extent to which fiscal revenue from tobacco excise can improve the economic welfare of cigarette workers. This study analyzes the impact of a cash transfer policy funded by the Tobacco Excise Revenue Sharing Fund, a fiscal mechanism that allocates excise revenue to local governments, on the economic welfare of cigarette workers in Kudus Regency. The research employs a qualitative approach based on primary data collected through in-depth interviews with six cigarette workers from three different companies. The analysis focuses on the distribution mechanism, benefit reception, and changes in workers’ economic conditions following the receipt of cash assistance. William N. Dunn’s policy evaluation framework is used to assess policy effectiveness in terms of outcomes and impacts. The findings indicate that the cash transfer policy contributes to short-term improvements in workers’ economic welfare, particularly in income support and the ability to meet household needs. These effects remain temporary because the policy primarily enhances purchasing power without strengthening workers’ economic capacity. This study recommends that local government design a more transformative cash assistance policy by integrating income support with economic empowerment initiatives for cigarette workers.